2013
DOI: 10.1021/ja400857g
|View full text |Cite
|
Sign up to set email alerts
|

π-Conjugated Heterotriangulene Macrocycles by Solution and Surface-supported Synthesis toward Honeycomb Networks

Abstract: A comparative analysis between a solution and a surface-mediated synthesis of heterotriangulene macrocycles is reported. The results show a preferential formation of the πconjugated macrocycles on surface due to two-dimensional confinement. The macrocycle prepared on a several hundred milligram scale by solution chemistry was characterized by single-crystal X-ray analysis and was furthermore extended toward next generation honeycomb species. Investigation of the photophysical and electronic properties together… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
93
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 96 publications
(99 citation statements)
references
References 61 publications
5
93
0
Order By: Relevance
“…The geometrical stability of the hexagonal macrocycles results from the non-covalent H-bonds and van der Waals interaction forces between the macrocycles, which allows them to adapt their equilibrium state19 and prevents the formation of pentagonal and heptagonal rings. Previously synthesized macrocycles on Ag(111)32 and Cu(111)33 were stabilized by an organometallic intermediate state that acts as a supramolecular template. We do not find any indication of an organometallic intermediate state in our experiments on Au(111) and hence we conclude that an organometallic template is no prerequisite for the geometrical stability of covalent six-membered macrocycles.…”
Section: Resultsmentioning
confidence: 99%
“…The geometrical stability of the hexagonal macrocycles results from the non-covalent H-bonds and van der Waals interaction forces between the macrocycles, which allows them to adapt their equilibrium state19 and prevents the formation of pentagonal and heptagonal rings. Previously synthesized macrocycles on Ag(111)32 and Cu(111)33 were stabilized by an organometallic intermediate state that acts as a supramolecular template. We do not find any indication of an organometallic intermediate state in our experiments on Au(111) and hence we conclude that an organometallic template is no prerequisite for the geometrical stability of covalent six-membered macrocycles.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we note that simple adaption of the method might also be expected to expedite the synthesis of related Bpinsubstituted planarized triphenylamines [19] and 2,6-substituted anilines [20] of pharmaceutical relevance, both of which otherwise require a two-step procedure of bromination and Pd-catalyzed Miyaura borylation. Key precursors Br-Pfp and Br-Tfp, required for modifying the boryl moiety, were prepared by Ir-catalyzed C-H borylation of 2,6-dimethylbromobenzene at the 4-position in 95% yield on a multi-gram scale, and subsequent Suzuki-Miyaura cross coupling with pentafluoroiodobenzene or 3,5-bis(trifluoromethyl)iodobenzene in 79-80% yield; notably, the borylation reaction was regiospecific and was, therefore, pivotal to ensuring high isolated yields of the products.…”
Section: Synthesismentioning
confidence: 99%
“…These compounds were characterized by multinuclear NMR spectroscopy, mass spectrometry, and elemental analysis. The room temperature 19 F{ 1 H} NMR spectrum of 4 shows three broad peaks at -50.4, -52.1 and -56.5 ppm (1:1:2) for the four CF3 groups of the FMes moieties that are in positions ortho to the boron atom and one singlet at -63.4 ppm for the two CF3 groups at the para-positions ( Figure S4), which indicates restricted rotation of the boron-bonded aryl rings. A similar phenomenon has been observed in our studies of Ar-B(FMes)2 compounds.…”
Section: Synthesismentioning
confidence: 99%
“…9). Here, one forms a honeycomb network 42 that, due to the design of the monomer, contains atomically precise pores [226][227][228]. Furthermore, we showed that it was possible to transform hexaiodo-functionalized cyclohexa-m-phenylene thin films into "super-honeycombs" and porous graphene structures by heating on a silver substrate.…”
Section: Graphene Nanoribbons: the Surface-bound Approachmentioning
confidence: 92%